THE IMPACT OF PRIVATE INVESTMENT IN THE CIRCULAR ECONOMY ON EU GDP - Aulonë Cenaj; Shenaj Haxhimustafa (Agora International Journal of Economical Sciences)
The main purpose of this research is to analyze the Impact of Private Investments in the Circular Economy on EU GDP for the period 2010-2020. This research has a sample of 28 EU Member States and analyzes a 10-year period. The scientific methodology applied in this study is the quantitative method. The data used in this research are secondary and are generated from official data published by Eurostat and the World Bank. Based on the results of this research, we may conclude that there is a negative relationship between private investments in the Circular Economy and the GDP of the European Union countries for the period 2010-2020. During the period 2010-2020, some EU countries experienced problems in attracting private investments due to difficult economic and political conditions, they had influenced private investments to have a negative effect on GDP.